2010
DOI: 10.1111/j.1432-2277.2010.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the attitudes and motivations of the Spanish population towards organ donation after death

Abstract: Summary Starting with the relevance of the Spanish experience, this study analyses the population’s disposition towards organ donation after death by means of a representative survey of the adult Spanish population (N = 1206, estimated error ±2.87%, P < 0.05). Of the participants, 8.1% were declared donors, 59.3% were likely to donate, 14.5% were against donating and 18.1% did not know or did not respond; 87.3% would donate relative’s organs if the deceased favoured donation, 50.2% if the deceased’s wishes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 35 publications
1
37
1
9
Order By: Relevance
“…The original instrument has been validated and used in diverse samples of general population in previous investigations (34,35). For this study, certain modifications were carried out and some new items were included on the basis of (i) the priorities expressed by those in charge of coordination and transplant of the National Organization of Transplants, (ii) the existing evidence in recent literature about the reasons and relevant variables for the decision to donate (6-10, 12, 15-17, 19, 20, 22-27, 29-45).…”
Section: Instrumentmentioning
confidence: 99%
“…The original instrument has been validated and used in diverse samples of general population in previous investigations (34,35). For this study, certain modifications were carried out and some new items were included on the basis of (i) the priorities expressed by those in charge of coordination and transplant of the National Organization of Transplants, (ii) the existing evidence in recent literature about the reasons and relevant variables for the decision to donate (6-10, 12, 15-17, 19, 20, 22-27, 29-45).…”
Section: Instrumentmentioning
confidence: 99%
“…There is also documented evidence that people who know or have contact with someone who has received or needed an organ transplant have a better attitude toward organ donation. 1,9 Similar donor attitudes have been reported for body donation for dissection. 7 The decision of a significant proportion of body donors (25%-33%) was influenced by having known somebody who had already donated or intended to donate his or her body for dissection.…”
mentioning
confidence: 51%
“…Although organ donation is aimed at helping patients improve their medical condition, body donation is mainly done for research and educational purposes. Two recently published studies have demonstrated that the majority of motives for organ donation originate from the wish to save other people's lives, 1 whereas the main motivation for body donation is related to the wish to be useful after death. 2 Nevertheless, both types of donation represent anatomical gifts that are extremely valuable to society.…”
mentioning
confidence: 99%
“…Incluso cuando ninguna religión se opone a la donación y, por el contrario, la consideran un acto libre y de generosidad hacia el prójimo. Así, el temor a ser mutilado o no participar de la resurrección compromete la decisión de ser donante (7,9,26,27,28) .…”
Section: Discussionunclassified